2019
DOI: 10.1186/s12917-019-1945-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre- and post-weaning dietary supplementation with arginine and glutamine on rabbit performance and intestinal health

Abstract: Background The purpose of the present study was to assess if the exposure to glutamine (Gln), arginine (Arg) or their combination from pregnancy, through the maternal diet, to a post weaning supplemented diet, can stimulate litter performance, gut development and immune function. To this end does and their litters were fed the same basal diet no supplemented (control C), or supplemented with 0.4% Gln, 0.4% Arg, or 0.4 Gln + 0.4 Arg. Rabbits were weaned at 25 d of age and fed the same experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Addition of inulin in a rabbit diet increase crypt depth and health of gut [43], supplementation of rabbit diet with whey powder increase gut health, but addition of citric acid, had no positive effect [44]. Also, an addition of 0.4% glutamine in a rabbit diet had a positive effect on intestinal villus high, but depended on the age of animals, the addition of arginine, and arginine and glutamine did not have the effect [45].…”
Section: Discussionmentioning
confidence: 99%
“…Addition of inulin in a rabbit diet increase crypt depth and health of gut [43], supplementation of rabbit diet with whey powder increase gut health, but addition of citric acid, had no positive effect [44]. Also, an addition of 0.4% glutamine in a rabbit diet had a positive effect on intestinal villus high, but depended on the age of animals, the addition of arginine, and arginine and glutamine did not have the effect [45].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dietary glutamine in healthy weaning piglets lowered the production of T H 2 cytokine IL-4 and increased the IFNγ/IL-4 ratio in mesenteric lymph node cells (153). Finally, in weaning rabbits, dietary glutamine upregulated IL-2 and IL-10 expression by IELs, while inhibiting expression of IL-6, an inducer of T H 2 differentiation of naïve T cells (174,175). Although further confirmation in neonatal animals is critical, these data may indicate that glutamine plays a role in promoting a more balanced T H 1/T H 2 immune system in the neonatal period.…”
Section: Impact Of Glutamine On Immune Cell Functionsmentioning
confidence: 95%
“…However, M-SJZG had noticeable effects on protection of it. This results indicated that M-SJZG might improve the survival rate from early weaning (Delgado et al, 2019). Previous studies have shown that dietary supplement such as Gln (positive group) could improve intestinal development and protect it from atrophy and injury under various stress conditions in young animals (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 60%